ChemInform Abstract: Catalytic Synthesis of Polyhydroquinolines by Lithium Perchlorate in Polyethylene Glycol. Issue 9 (4th March 2014) - Wu, Chunlei; Shen, Runpu; Tao, Feifei; Gao, Xiaozhong; Deng, Liping; Zhou, Yubo
Abstract An effective synthesis of polyhydroquinoline derivatives via a four‐component one‐pot reaction of aromatic aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate is presented.